Biofermentasi Limbah Ternak Menjadi Pupuk Biorganik dan Biopestisida untuk Mendukung Pertanian Organik di Desa Buahan Kaja Payangan Gianyar - N. W. Siti; Ni M. Witariadi; N. G K. Roni; Ni N. Candraasih K (Buletin Udayana Mengabdi, 2016)
Community service activities that aim to improve the knowledge and skills of farmers in processing animal waste into biorganik fertilizer and biopesticides in support of orgnaik agriculture in the village Buahan Kaja, Payangan Gianyar. This community service has been carried out in groups of Subak Abian Buahan Kaja village on Wednesday, June 24, 2015. The method used is the extension and demonstration on how to process cow feces and urine by microbial fermentation method using effective and the introduction of Standard Operational Procedures (SOP) for organic farming. Results of devotion are: (1) the level of knowledge of farmers on fermentation technology for processing animal waste increased from 20% to 80%; (2) during the discussions 40% of group members to ask questions about the role of effective microbes in the urine and feces of cattle; (3) at the demonstration 90% Subak Abian groups already understand how to process animal waste into bioorganic fertilizer and biopesticides; (4) groups of Subak Abian 80% have been able to make bioorganic fertilizer and biopesticides and apply for her own garden, but the farmers have not been able to sell the products produced; (5) establishment of demonstration plots measuring 50 are of organic citrus. From the results of devotion can be concluded that (1) the knowledge and skills of Subak Abian group increases, (2) groups of Subak Abian been able to produce bioorganic fertilizer and biopesticides and (3) the realization of demonstration plots of organic citrus.